2020
DOI: 10.1186/s13063-020-04553-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of olanzapine to treat agitation in traumatic brain injury: study protocol for a randomised controlled trial

Abstract: Background: Agitation is common in the early stages of recovery from traumatic brain injury (TBI), when patients are in post-traumatic amnesia (PTA). Agitation is associated with risk of harm to patients and caregivers. Recent guidelines recommend that agitation during PTA is managed using environmental modifications. Agitation is also frequently treated pharmacologically, with the use of atypical antipsychotics such as olanzapine among the most common. This is despite a lack of well-designed studies to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…These guidelines also suggest not routinely using haloperidol or atypical antipsychotics to treat delirium. Notably, olanzapine has not been demonstrated to impair cognition after TBI and is currently the subject of a randomized controlled trial for post-traumatic agitation [ 167 ].…”
Section: Management Principlesmentioning
confidence: 99%
“…These guidelines also suggest not routinely using haloperidol or atypical antipsychotics to treat delirium. Notably, olanzapine has not been demonstrated to impair cognition after TBI and is currently the subject of a randomized controlled trial for post-traumatic agitation [ 167 ].…”
Section: Management Principlesmentioning
confidence: 99%
“…Moreover, suppression of dopaminergic neurotransmission can be unfavorable for posttraumatic arousal as clinical trials in amantadine have shown efficacy (12). The ongoing randomized controlled clinical trials using antipsychotics to treat posttraumatic agitation in subacute rehabilitation settings may shed light on the management of emotional dysregulation as a result of sTBI (23,24). The treatment of posttraumatic agitation in acute hospital setting requires further large-scale prospective randomized studies with long-term follow up.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that dopaminergic suppression interferes with arousal and consequently recovery of consciousness. Currently, two randomized controlled clinical trials are being conducted to evaluate the safety and efficacy of antipsychotics in sTBI patients in rehabilitation settings (23,24). Results from these studies can shed light on the underlying mechanism of agitation during the early stage of recovery from sTBI.…”
Section: Introductionmentioning
confidence: 99%